Determination of Molybdenum in Soil, Coal and Industrial Residue Samples by Flame Atomic Absorption Spectrometry - Yigmatepe, Ergul; Avci, Halim; Yaman, Mehmet (Asian Journal of Chemistry, 2010)
This paper proposes a procedure for mineralization and determination of trace amounts of molybdenum in various solid samples. The samples including soil, coal and slag of power plants, furnace residue of the thermoelectric power plant and other industrial solid residues were collected from 8 different cities of Turkey. Molybdenum was extracted from matrices by conventional open wet digestion procedure. For this purpose, aqua regia was used as digestion solvent. Molybdenum concentrations in clear solution were determined by flame atomic absorption spectrometry. The determined Mo concentrations were found to be in range of 0.18 and 0.29 mu g/g for soil. 4.9 and 54.6 mu g/g for coal, 9.9 and 32 mu g/g for power plants slag and 27.8-2295 mu g/g for industrial residue samples. To establish the validity of the results. the recoveries from solid samples fortified with Mo were found to be at least 90%. The effect of contamination was eliminated by subtracting the values obtained for blanks.
Keywords: Molybdenum; Industrial residue; Coal; Soil; Flame atomic absorption spectrometry